Administration of Curcuma Xanthorrizha (Temulawak) Jelly Increases the Body Weight of Undernourished Toddlers - Sri Mahasari, Marwinda; Agustina, Lusinta; Widhi Astuti, KH Endah (Jurnal Kebidanan dan Kesehatan Tradisional, 2024)
Background: Malnutrition in toddlers remains a public health challenge because it can hinder children's growth and development. One of the main causes is low appetite, which leads to inadequate nutritional intake. Temulawak (Curcuma xanthorrhiza) is known to have properties that improve digestive function and increase appetite through its curcuminoid content, which acts as an antioxidant. This study aims to determine the effect of Curcuma xanthorrhiza jelly on weight gain in malnourished toddlers in Krajan Village, Jatinom, Klaten.  Methods: This study used a quantitative design with a quasi-experimental design and a pretest-posttest approach with a control group. The sampling technique used was total sampling with 17 toddler respondents, consisting of 9 toddlers in the intervention group and 8 toddlers in the control group. The research instrument was a weight observation sheet, while data analysis was performed using the Mann–Whitney nonparametric test.  Results: The analysis results showed a higher increase in weight in the intervention group compared to the control group, with a statistically significant difference (p-value 0.013).  Conclusion: There is a significant effect of Curcuma xanthorrhiza jelly administration on weight gain in malnourished toddlers. It is recommended that innovations in the administration of natural herbal ingredients such as temulawak be developed in the form of safe and attractive functional food products to improve the nutritional status of toddlers.